Renal Vein Thrombosis as a Presenting Sign in a Boy with Lupus Nephritis- Case Report (Global Journal of Medical Research, 2021)
Renal vein thrombosis (RVT) is a rare phenomenon that involves the renal veins or their tributaries. Beyond the neonatal age, it can be associated with several conditions such as coagulopathy, nephrotic syndrome, and autoimmune diseases, which include antiphospholipid syndrome and systemic lupus erythematosus (SLE). We describe a case of an 11-year-old boy presenting with abdominal pain and diagnosed with renal vein thrombosis as a presenting manifestation of membranous lupus nephritis. RVT as a presenting sign of SLE has been reported only in few cases and, to our knowledge, never in a male pediatric patient. Thrombotic complications responded to intense immunosuppression combined with an anticoagulation treatment regimen, but nephrosis persisted. High degree of suspicion is required for prompt diagnosis of this rare and clinically challenging condition.
Keywords: renal vein thrombosis; systemic lupus erythematosus; membranous lupus nephritis; pediatric case report; rheumatology